Faktor-Faktor Yang Berhubungan Dengan Kejadian Perdarahan Postpartum Di Kota Palu - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT Postpartum bleeding has been the main cause of maternal death in developing countries. In Indonesia, the main causes of maternal death are due to the followings 40% bleeding, 30% infection and 20% eclampsia. Among bleeding cases atonia uteri is the most frequent cause. In Palu, most frequent referred cases of parturition attributed to postpartum bleeding was 32,17%. The present research was aimed to identify factors related to postpartum bleeding. It belonged to hospital based observational research using unmatched case-control design. Subjects consisted of 77 cases and 154 controls. Cases were maternal parturitions with postpartum bleeding hospitalised or referred to hospital. Controls were normal parturitions in hospital and the community. Risk factors studied were nutritional status, anaemia, maternal age, antenatal care, parity, birth interval, bad previous parturition, birth attendant, pregnancy age and parturition duration. Data processing was performed using descriptive and statistic analyses, namely univariate, stratified and multivariate analyses. Results proved that risk factors of postpartum incidence were anaemia with OR=4,83 (95% CI: 2,24